Perancangan Sistem Informasi Pelayanan dan Administrasi Klinik (Studi Kasus : Klinik X di Kabupaten Malang) - Miftakul Fira Maulidia; Besral Besral; Artha Prabawa (Politeknik Negeri Jember, 2023)
Primary clinics that are supported by a good management information system are important in this era. Clinic X is a primary clinic with General Poly and Maternal and Child Health (MCH) services, Emergency Room (ER) and One Day Service. In a month the average number of patients visiting is 1500-2000 people. There are 9 health workers. The recording system is done manually using paper, double data often occurs. Only the register entered in the computer’s Excel column is useful for storing medical record numbers. Based on the suggestion box, patients complained of long waiting times. Therefore, a clinical administration and service information system was developed. The system was developed using the Systems Development Life Cycle (SDLC) method with a prototyping approach. The preparation stage starts from the planning stage to the design stage. The result of this system is patient data and examination information; dashboards related to patients, clinic stock and logistics, as well as clinic finances